Challenges and Innovations of the GTK MA Sub-directorate of the Ministry of Religion in Exploring the Capabilities of Madrasah Teachers in the Independent Curriculum - Rafik; Subiyantaro (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to explore the challenges faced by the Subdirectorate of Teachers and Education Personnel (GTK) Madrasah Aliyah (MA) of the Ministry of Religion in exploring the capabilities of madrasa teachers towards the Independent Curriculum, as well as the innovations made in dealing with them. these challenges. Using a qualitative approach, this research analyzes data from interviews with relevant stakeholders at the Ministry of Religion, participatory observation and documentation studies. In the context of education in Indonesia, developing teacher capabilities is crucial in ensuring the implementation of quality learning. Moreover, with the introduction of the Independent Curriculum as an effort to transform national education, the challenges faced by the Subdirectorate of Teachers and Education Personnel (GTK) of Madrasah Aliyah (MA) at the Ministry of Religion are increasingly complex. This article discusses the main challenges faced by the GTK MA Subdirectorate of the Ministry of Religion in exploring the capabilities of madrasa teachers towards the Independent Curriculum, as well as the innovations made to overcome these challenges.